2013
DOI: 10.1200/jco.2012.47.0302
|View full text |Cite
|
Sign up to set email alerts
|

African American Men With Very Low–Risk Prostate Cancer Exhibit Adverse Oncologic Outcomes After Radical Prostatectomy: Should Active Surveillance Still Be an Option for Them?

Abstract: A B S T R A C T PurposeActive surveillance (AS) is a treatment option for men with very low-risk prostate cancer (PCa); however, favorable outcomes achieved for men in AS are based on cohorts that under-represent African American (AA) men. To explore whether race-based health disparities exist among men with very low-risk PCa, we evaluated oncologic outcomes of AA men with very low-risk PCa who were candidates for AS but elected to undergo radical prostatectomy (RP). Patients and MethodsWe studied 1,801 men (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
171
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(184 citation statements)
references
References 28 publications
6
171
1
6
Order By: Relevance
“…A recent Johns Hopkins study [7] compared AA and Caucasian men diagnosed with very low-risk PCa who underwent immediate RP and found that AA race was strongly and independently associated with upgrade and upstage after surgery. While these findings were notable because favorable outcomes had been expected among such a low-risk group, the cohort was from a single academic institution, which may limit the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Johns Hopkins study [7] compared AA and Caucasian men diagnosed with very low-risk PCa who underwent immediate RP and found that AA race was strongly and independently associated with upgrade and upstage after surgery. While these findings were notable because favorable outcomes had been expected among such a low-risk group, the cohort was from a single academic institution, which may limit the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite improvements in clinical and pathologic assessment, there are considerable levels of upgrading and upstaging between biopsy and radical prostatectomy (RP). Upgrading and upstaging are well described in men otherwise eligible for AS who undergo surgery instead as primary treatment [6,7]. Depending on the criteria for defining AS eligibility, upgrading occurs in 23-35% of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also somewhat contradictory given the higher rates of pathological upgrading after radical prostatectomy in African-American men with low-risk disease. 29 Moreover, adverse oncologic outcomes and lower biochemical recurrence-free survival are also reported after radical prostatectomy in African-American men. 30 Despite persistent efforts to tackle these issues, there are still significant mortality differences in prostate cancer among ethnic groups.…”
Section: Management and Outcomesmentioning
confidence: 99%
“…The genetic contribution to PCa disparity has been well established with the identification of significant racial differences in frequency and expression of various genes and biomarkers. Recently, several biomarkers (Table 1) have been shown to correlate with aggressive phenotypes in prostate cancer [15][16][17][18][19][20][21][22] . The most notable examples include the TMPRSS2:ERG gene fusion 23 , Ki-67 expression 17 , and biomarkers involved in androgen metabolism 8,18 .…”
Section: Introductionmentioning
confidence: 99%